Նշենու հիվանդությունները ՀՀ Արմավիրի մարզի Երվանդաշատ համայնքի պայմաններում - Ավագյան, Գ. Վ.; Սահակյան, Վ. Գ. (ՀԱԱՀ հիմնադրամ)
В условиях общины Ервандашат РА в 2021-2022 гг. были изучены видовой состав болезней миндаля и зараженность различных сортов. Деревья сорта Гуара были заражены дырчатой пятнистостью косточковых, гоммозом и пенообразным раком, миндаль сорта Пента – гоммозом, ожогом листьев, пенообразным раком, хлорозом, а на деревьях сорта Лоран болезней не обнаружено. Заболевания ожог листьев и пенообразный рак миндаля в Армении были зарегистрированы впервые. Из зараженных гоммозом образцов был выделен и идентифицирован ряд фитопатогенных (Arthrinium sp./Apiospora sp., Fusarium acuminatum, F. Incarnatum-equiseti, F. oxysporum, Valsa sordida) и непатогенных (Clonostachys rosea, Lachancea quebecensis, Mucor circinelloides, Pichia kudriavzevii, Torulaspora sp.) грибов. As a part of the research, the species composition of almond diseases, as well as the susceptibility of different almond varieties, was studied. The following diseases and pests were detected at Armavir Marz: shot hole disease, almond leaf scorch, foamy canker, chlorosis, gummosis, peach twig borer, and green peach aphid. Trees of the Guara variety were infected with shot hole and gummosis, Penta - with gummosis, leaf scorch, and chlorosis. Diseases were not detected in trees of the Lauranne variety. Almond leaf scorch (Xylella fastidiosa Wells et al.) and foamy canker (Zymomonas Kluyver and van Niel) diseases were recorded in Armenia for the first time. Plant pathogenic fungi Arthrinium sp./Apiospora sp., Fusarium acuminatum, F. Incarnatum-equiseti, F. oxysporum, Valsa sordida (Cytospora chrysosperma), as well as non-pathogenic fungi Clonostachys rosea, Lachancea quebecensis, Mucor circinelloides, Pichia kudriavzevii and Torulaspora sp. have been isolated and identified from almond branches and trunks infected with gummosis.
Keywords: Ագրոնոմիա և ագրոէկոլոգիա